Predicting Price Level Dynamics in Cambodia: A Scenario Analysis - Ky, Sereyvath; Flores, Edman; Lim, Siphat (Journal of Ecohumanism, 2024)
This study aims to conduct a comprehensive scenario analysis to predict the dynamics of price levels in Cambodia. Employing a Vector Autoregression (VAR) model, the study examines the relationships among the inflation rate, foreign exchange rate, and money supply. Rigorous unit root testing and lag order selection ensure the appropriateness and accuracy of the modeling approach. The analysis reveals cyclical patterns and mean-reverting properties among inflation, foreign exchange rates, and money supply growth, emphasizing the need for proactive monetary policy measures by the National Bank of Cambodia. The empirical results indicate that foreign exchange rate fluctuations significantly influence inflation, underscoring the importance of effective foreign exchange rate management for domestic price stability. Additionally, variations in money supply impact inflation and foreign exchange rates, highlighting the significance of prudent monetary management for economic growth and price stability. The study underscores the necessity for policymakers' vigilance in responding to the dynamic interactions among inflation, foreign exchange rates, and money supply to stabilize the economy. The study acknowledges limitations, including the focus on quarterly data and the VAR model's assumptions of linear relationships and stationary data, and proposes future research directions to further enhance the understanding of price level dynamics in Cambodia.